EFEKTIVITAS PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI KEANEKARAGAMAN BUDAYA - Nurhaliza, Adinda Putri; Agustinaswara, Siti Rostika (Sindoro: Cendikia Pendidikan, 2025)
This study aims to analyze how the Problem Based Learning (PBL) learning model affects students' learning outcomes with the topic of cultural diversity. The PBL method is an approach that emphasizes students' activeness in learning to solve relevant problems and aims to improve critical thinking skills, collaboration, and deep understanding in students. Cultural diversity is an important material to build an attitude of tolerance, respect differences between tribes, and foster a sense of love for the homeland in students. This study employs a literature review method by examining various articles and scientific journals discussing the effectiveness of PBL in teaching cultural diversity. Findings indicate that the PBL model can improve students' learning outcomes in cognitive, affective, and social aspects. The implementation of PBL also increases student engagement and motivates them to understand cultural diversity more thoroughly through problem exploration and group discussions. Furthermore, applying the PBL model positively influences students’ attitudes, fostering openness to cultural differences and developing strong social skills.